Types and Efficacy of Laboratory Tests for Diagnosing Peanut Allergy: A Systematic Review - Ahaleed Arkook, Lujain Arkook (South Eastern European Journal of Public Health, 2025)
Background: Between 2 and 10% of people worldwide suffer from food allergies; the prevalence varies by age, location, and diagnostic technique. Challenges in the diagnosis of food allergies are said to be as common in Asia and Africa as they are in Western countries. Additionally, there is growing evidence that prevalence is increasing in developing countries. Double-blind food challenges are considered to be the gold standard in the diagnostic process, but they are risky and time-consuming. From objective symptoms to subjective ones (from urticaria and cough to severe systemic allergic reactions with wheezes or anaphylaxis), occurrences following the test were reported. Objectives: In order to summarize and assess the different laboratory tests and their different parameters in the diagnosis of food allergies, particularly peanut allergies, we carried out this systematic review. These tests included the mast cell activation test (MAT), specific immunoglobulin E (sIgE) tests, component-resolved diagnostics (CRD), and the basophil activation test (BAT). Methods: We conducted a comprehensive search in PubMed, Web of Science, and Scopus to identify studies evaluating laboratory tests for diagnosing peanut allergy. We selected studies according to inclusion and exclusion criteria. Data on diagnostic performance metrics were extracted. The risk of bias was assessed using the QUADAS-2. Results: The inclusion criteria were met by 11 research studies with 1170 participants. When compared to other current laboratory tests such as the skin prick test, sIgE, and basophil activation test (BAT), the mast cell activation test (MAT) was found to be the most accurate diagnostic tool for peanut allergy diagnosis. It may even be able to replace the conventional oral food diagnostic tests (OFCs). However, it is novel and still under research, and its cost and accessibility are still restricted. By using BAT, we may use CD63 peanut/anti-IgE and CD-sens to determine the severity and threshold of allergic reactions during OFCs. Conclusion: Mast cell activation test offers superior accuracy in the diagnosis of peanut allergy and can help confirm diagnoses. A multi-test approach that incorporates these tools can enhance diagnostic accuracy, reduce the risk of overdiagnosis, improve patient management, and decrease the need for risky OFCs.